Implementación de un sistema web mediante el uso de herramientas opensource para gestionar los procesos de mantenimiento de maquinaria en la empresa Cedal s.a. ubicada en el cantón Latacunga provincia de Cotopaxi durante el periodo académico agosto 2015 – febrero 2016 - Mosquera Velásquez, Diego Patricio (2016)
By elaborating this research has been design and establish correctly the application of a informatics system through the systematization of the different work orders of maintenance staff and following-up of the machinery within company; using OpenSource tools. The primary aim of this project is to facilitate the tracing and control management of the processes of machinery maintenance at CEDAL S.A Company. With the implementation of this web system has managed to optimize the work time at the moment of making the follow-up all the machineries maintenance, which will increase the productivity and efficiency of the maintenance area, these follow-ups are carried out manually and are very complex because they must manage the maintenance and the elaboration of reports, summaries and comparative reports that are very necessary for the functioning analysis of each machinery at the company. This project will improve the control of the machines and the elaboration of work orders for the people responsible to do the maintenance, with this one has managed to improve the learners’´ knowledge who are responsible of the elaboration of this project, which will allow an integration between theory and internship.